Changing roles for a new psychotherapy - Miller, John G., 1928- (Routledge/Taylor & Francis Group, 2013)
"Psychotherapy is not a 'one size fits all approach.' As author John Miller describes in Changing Roles for a New Psychotherapy, all theoretical orientations have their uses and merits in different situations and with different clients. Through a varied personal life and professional career, in which he developed a creative psychotherapeutic approach that allows the adaptation of diverse roles with clients, Dr. Miller has gained insights through working in academia, the sciences, management consulting, and a state hospital. He applies these insights, along with those he gained working various summer jobs, to take readers beyond the standard medical model of diagnosis and treatment by drawing on the roles of other professionals. He examines 11 different occupations and explores how the insights gained in each field can enhance therapeutic possibilities. How does cooking relate to psychotherapy? Can accounting change the way psychotherapy is performed? Read on to find out!"--